The Role of the Regional Health Office in the COVID-19 Patient Referral System - Yanto Maulana (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
This study investigates the pivotal role played by the Regional Health Office of North Sulawesi Province in managing the COVID-19 patient referral system. The COVID-19 pandemic has placed immense pressure on healthcare systems worldwide, necessitating efficient coordination and management of patient referrals to ensure timely and appropriate care. The Regional Health Office of North Sulawesi Province plays a critical role in overseeing and optimizing the patient referral process, which includes triage, transportation, and coordination among healthcare facilities. This research aims to analyze the effectiveness and challenges faced by the Regional Health Office in managing COVID-19 patient referrals, with a focus on improving the overall healthcare response to the pandemic.